2023
DOI: 10.1080/14756366.2023.2205052
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin analogues exert potent inhibition on human and rat gonadal 3β-hydroxysteroid dehydrogenases as potential therapeutic agents: structure-activity relationship and in silico docking

Abstract: Curcuminoids are functional food additives, and the effect on gonadal hormone biosynthesis remains unclear. Gonads contain 3β-hydroxysteroid dehydrogenase isoforms, h 3β-HSD2 (humans) and r3β-HSD1 (rats), which catalyse pregnenolone into progesterone. The potency and mechanisms of curcuminoids to inhibit 3β-HSD activity were explored. The inhibitory potency was bisdemethoxycurcumin (IC 50 , 1.68 µM) >demethoxycurcumin (3.27 µM) > curcumin (13.87 µM) > tetrahydrocur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The results of higher anti-melanogenic activity of BDC than PC, DC, and THC, with a differential efficacy of BDC in mouse and human cells, are reminiscent of the results of a previous study [71] that demonstrated that BDC emerged as the most potent inhibitor of the activity of the 3β-hydroxysteroid dehydrogenase enzyme compared to THC, PC, and DC, with a differential efficacy across human and rat species. Notably, the two other compounds, THBDC and THDC, were not examined in their study; hence, it remains unknown if THBDC may have been superior to BDC in their assays.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The results of higher anti-melanogenic activity of BDC than PC, DC, and THC, with a differential efficacy of BDC in mouse and human cells, are reminiscent of the results of a previous study [71] that demonstrated that BDC emerged as the most potent inhibitor of the activity of the 3β-hydroxysteroid dehydrogenase enzyme compared to THC, PC, and DC, with a differential efficacy across human and rat species. Notably, the two other compounds, THBDC and THDC, were not examined in their study; hence, it remains unknown if THBDC may have been superior to BDC in their assays.…”
Section: Discussionsupporting
confidence: 71%
“…LogP values are a measure of the lipophilicity of a drug and are useful in SAR studies [72]. In the previous study [71], it was also shown that the higher inhibitory effects of BDC were correlated to its lower logP values and, thus, lower lipophilicity, leading the authors to suggest that removing both methoxy groups is expected to increase potency. Our findings of the higher capacity of BDC or THBDC (both demethoxylated) inhibiting tyrosinase activity and melanogenesis can be attributed to the removal of both of their methoxy groups, which enables the hydroxyl groups to form hydrogen bonds more easily with the tyrosinase enzyme, thereby enhancing their inhibitory potency.…”
Section: Discussionmentioning
confidence: 99%